Polyvinyl chloride modifications, properties, and applications: Review. (5th March 2022) - Lieberzeit, Peter; Bekchanov, Davron; Mukhamediev, Mukhtar
Abstract: The present study provides an overview of the latest scientific developments in the field of application and modification of ion exchange sorbents and membranes made of granular and powdery polyvinyl chloride (PVC), focusing on some scientific works, such as water and wastewater treatment, ion exchange, gas separation, etc. For this purpose, an introduction to the various methods of modifying PVC is first given, and then the application of ion exchange sorbents and membrane is discussed. Methods of modification of PVC under homogeneous and heterogeneous conditions using modifiers containing N, S, and O atoms are also described. Various ion‐exchange sorbents and membranes based on PVC, methods for modifying PVC and the use of the obtained ion‐exchange sorbents and membranes are viewed. A comparison of the sorption properties of ion‐exchange sorbents based on PVC and sorbents used in industry has also been carried out.